An analysis of the spontaneous mutation rate measurement in filamentous fungi - Baracho,Marta S. (2003)
Mutations related to gene methG1 of Aspergillus nidulans were analyzed, in order to study a mathematical model for the determination of the mutation rate per nucleus per generation, in filamentous fungi. A replica plating technique was used to inoculate, in a single operation, 26 colonies of the strain, into Petri dishes containing culture medium, and the nine central colonies were analyzed for size and number of conidia in each colony. Using this technique, several central colonies were analyzed with regard to the appearance of mutation, and the number and type of reversions were determined for each colony. The frequencies obtained for each reversion were analyzed, in order to verify if their distribution was in accordance with that of Greenwood and Yule. The data obtained allowed us to conclude that, using the mathematical model studied, it is possible to determine the mutation rate per nucleus, per generation, in filamentous fungi.